A TRANSITIVITY ANALYSIS ON STUDENTS’ WRITING RECOUNT TEXT - Septyana D Sianipar; Siti Aisah Ginting; Tiarnita M. S Siregar (Universitas Negeri Medan, 2021)
A TRANSITIVITY ANALYSIS ON STUDENTS’ WRITING RECOUNT TEXT *Septyana D Sianipar ** Siti Aisah Ginting ** Tiarnita M. S Siregar Abstract The objectives of this study were to find out the types of transitivity system used on students’ writing recount texts. Further, this study also aims to identify the types of transitivity systems realized in students’ writing recount texts. This study was conducted by using a descriptive qualitative design method. The data were 15 pieces of recount texts written by tenth grade students of SMAN 21 Medan being analyzed as the data. From this research, it was found that in all units of students’ writing recount texts, there were 249 clauses. In these clauses, all process types can be found with varieties of the usage, they were: material process, mental process, relational process, behavioral process, verbal process, and existential process. As for the participants, almost all can be found in students’ recount texts: actor, goal, range, senser, phenomenon, token, value, carrier, attribute, possessor, possessed, behaver, sayer, verbiage, existent, and beneficiary ones. Only two participants were not found in the texts: the range and the target ones. As for circumstances, there were seven circumstances found in the students’ recount texts: extent, location, manner, cause, accompaniment, and matter. The contingency, angle, and role aspects however, were not found. The realization of the transitivity system on students writing recount texts, were found with varieties of the usage in constructing language features of the students’ recount texts. The processes were realized by personal pronoun, direct and indirect objects. Finally, the circumstances were realized by prepositional and adverbial phrases. Keywords: Transitivity System, Writing, Students’ recount texts.